2021
DOI: 10.1371/journal.pone.0249218
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of precancerous cervical lesions: The role of women’s socio-demographic, sexual behavior and body mass index in Amhara region referral hospitals; case-control study

Abstract: Background Cervical cancer remains one of the major public health challenges in low and middle-income countries including Ethiopia. There was a scarce of evidence regarding the effect of woman’s socio-demographic characteristics and body mass index on the development of precancerous cervical lesions in Ethiopia. Therefore, the current study aimed at identifying the risk factors of precancerous cervical lesions among women visiting referral hospitals for cervical cancer screening in Amhara national regional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…The knowledge was better than the study of Minhas et al 13 , this study revealed 3% knowledge about cervical cancer screening among females of Punjab, Pakistan. On the contrary Ozcan H et al; 23 revealed that 48.6% Turkstat had knowledge of screening of CA cervix and 16.2% received this knowledge from healthcare provider. Regrettably; PAP smear testing has not been implemented properly in Pakistan.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 90%
“…The knowledge was better than the study of Minhas et al 13 , this study revealed 3% knowledge about cervical cancer screening among females of Punjab, Pakistan. On the contrary Ozcan H et al; 23 revealed that 48.6% Turkstat had knowledge of screening of CA cervix and 16.2% received this knowledge from healthcare provider. Regrettably; PAP smear testing has not been implemented properly in Pakistan.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 90%
“…This study was restricted to African countries because the sexual behavior of this population was varied from developed regions and other parts of the world (for instance developed countries have late age at first sexual intercourse [ 35 , 36 ] and the study site was therefore excluded from this analysis. Besides, early marriage is a culture and commonly practiced in the African population which has a relation with the development of cervical cancer [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the available literature consistently showed age is another risk factor for developing cervical cancer since cervical cancer occurs mainly after the middle life of women [ 15 , 25 , 26 ]. However, there has been some conflicting findings in the literature about whether early sexual intercourse is linked to cervical cancer [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased access to antiretroviral therapy (ART) has increased the life expectancy of women living with HIV, but many remain susceptible to high-risk HPV infection, persistence, cervical lesion incidence and progression to carcinoma of the cervix (24). The association between HIV and premalignant cervical lesions is moderated by several other factors, such as early age of rst sexual debut, multiple sexual partners, previous history of sexually transmitted infections (e.g., chlamydia infections), level of education, oral contraceptive use, multiparity, smoking and low body mass index (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%